Synaptosomal membrane-based Langmuir-Blodgett films: A platform for studies on γ-aminobutyric acid type A receptor binding properties - Turina, Anahi del Valle (2015)
In this work we used Langmuir-Blodgett films (LB) as model membranes to study the effect of molecular packing on the flunitrazepam (FNZ) accessibility to the binding sites at the GABAA receptor (GABAA-R). Ligand binding data were correlated with film topography analysis by atomic force microscopy images (AFM) and SDS-PAGE. Langmuir films (LF) were prepared by the spreading of synaptosomal membranes (SM) from bovine brain cortex at the air-water interface. LBs were obtained by the transference, at 15 or 35 mN/m constant surface pressure (π), of one (LB15/1c and LB35/1c) or two (LB35/2c) LFs to a film-free hydrophobic alkylated substrate (CONglass). Transference was performed in a serial manner, which allowed the accumulation of a great number of samples. SDS-PAGE clearly showed a 55 kDa band characteristic of GABAA-R subunits. Detrended fluctuation analysis of topographic data from AFM images exhibited a single slope value (self-similarity parameter α) in CONglass and a discontinuous slope change in the α value at an autocorrelation length of ∼100 nm in all LB samples, supporting the LF transference to the substrate. AFM images of CONglass and LB15/1c exhibited roughness and average heights that were similar between measurements and significantly lower than those of LB35/1c and LB35/2c, suggesting that the substrate coverage in the latter was more stable than in LB15/1c. While [3H]FNZ binding in LB15/1c did not reach saturation, in LB35/1c the binding kinetics became sigmoid with a binding affinity lower than in the SM suspension. Our results highlight the π dependence of both binding and topological data and call to mind the receptor mechanosensitivity. Thus, LB films provide a tool for bionanosensing GABAA-R ligand binding as well as GABAA-R activity modulation induced by the environmental supramolecular organization.